Avancée dans la prévention des « chutes de plain-pied » au travail - Sylvie Leclercq; Michel Monteau; Xavier Cuny (Perspectives Interdisciplinaires sur le Travail et la Santé)
Falls on the same level remain frequent and serious occupational accidents. The terminology used to describe these accidents is varied and somewhat imprecise. Moreover it does not integrate the variety of accidents with different names. The advantage of considering an occupational accident category with motion perturbation (MPA) is demonstrated, based on extracts from various occupational accident accounts. A model is then proposed for MPAs that shows that in these specific cases of accidents, the injury often results from a fortuitous association between the victim’ perturbed motion energy and a physical element that causes injury due to its properties and subsequently called a “circumstantial hazard”. Finally, the reasoning behind the MPA classification is explained. In particular, it appears that prevention that focuses on the immediate causes of the injury is difficult, even impossible, in MPA cases, essentially because of requirements inherent in the work and the constraints on the enterprise to implement this prevention. Prevention implemented at the source of the risk therefore seems to be the only feasible solution. From commonplace accidents, MPAs reveal dysfunctions within the production system.